The Knowledge Level of Primiparous Mothers About Newborn Baby Care at the Pratama Kasih Ibu Clinic in Jaharun B Village, Galang District in 2020 - Oktafiana Manurung; Meyana Marbun; Sri Rahma Friani (Institute of Computer Science (IOCS), 2021)
Efforts to create a healthy life must start from a baby because at this time there is a rapid growth and development that determines growth and development in adulthood. Mothers must prepare themselves by increasing their knowledge in caring for newborns, because the mother's ability to care for newborns is influenced by mother's knowledge from the beginning, if the mother does not have good knowledge, the mother will have difficulty in carrying out new roles as a mother. This study aims to find out the description of knowledge of Primipara's mother about the care of a newborn baby at the Pratama Kasih Ibu clinic 2020 in caring for a newborn baby. This research is conducted with a descriptive method, sampling is carried out by taking the entire population, namely 30 primiparous mothers are examined (Total Sampling). Based on the results of the research, the Respondents' knowledges of newborn care with good knowledge are 5 people (16.7 %), and Respondents with less Knowledge are 6 people (20%) . Based on the results of the study, it can be found that the majority of Primipara mothers get information from friends, not from health workers, so it is advisable for health workers or the local government to provide counseling or care about newborn baby care.